Loading ...
Sorry, an error occurred while loading the content.

2a. HARDY LITTLEWOOD CONJECTURE ANALISYS. FIRST PROPOSITION.

Expand Messages
  • Kermit Rose
    ... [Meaning if p = 1 mod 6, k = (p-1)/6, and if p = 5 mod 6, (k = (p+1)/6. ... Simple proof: In case p = 6 k + 1, and n = 6 j + 1 pn + k = (6 k + 1) * (6 j +
    Message 1 of 1 , Jan 6, 2011
    • 0 Attachment
      > 2a. HARDY LITTLEWOOD CONJECTURE ANALISYS. FIRST PROPOSITION.
      > Posted by: "ALBERTO" arfzelaya@... albrtzlya
      > Date: Wed Jan 5, 2011 6:25 pm ((PST))

      > Let p any prime of the form 6k+-1

      [Meaning if p = 1 mod 6, k = (p-1)/6, and if p = 5 mod 6, (k = (p+1)/6.

      > and n any integer number
      > and k the k value corresponding to each prime of the form 6k+-1

      > (for instance k values corresponding to prime 5 is 1 because 5=(6*1)-1
      > and k value for 109 is 18 because 109=6*18+1)

      > Therefore the algebraic expression
      > pn+-k is equivalent to 6ab+-a+-b


      Simple proof:

      In case p = 6 k + 1, and n = 6 j + 1
      pn + k
      = (6 k + 1) * (6 j + 1) + k
      36 j k + 6 j + 6 k + 1 + k
      = 6 k (6 j + 1) + (6 j + 1) + k ; a = k; b = 6j + 1;

      In case p = 6 k + 1, and n = 6j - 1
      pn - k
      =(6k+1)(6j-1) - k
      =36 k j + 6 j - 6 k -1 - k
      = 6 k (6 j - 1) + (6 j - 1) - k; a = k; b = 6 j - 1

      In case p = 6 k - 1, and n = 6 j + 1
      pn - k
      = (6 k - 1) (6 j + 1) - k
      = 36 k j + 6 k - 6 j - 1 - k
      = 6 k (6 j + 1) - (6 j + 1) - k ; a = k; b = (6j+1)


      In case p = 6k -1, and n = 6 j - 1
      pn + k
      = (6k - 1)(6j-1) + k
      = 36 kj - 6 k - 6 j + 1 + k
      = 6 k (6j - 1) - (6j-1) + k ; a = k, b = (6 j - 1)



      > In other words if an integer x is not equal to pn+-k it won't be
      > equal to 6ab+-a+-b

      Proof of if and only if:

      If p = 6 k + 1, and b = n, and a = k,
      then
      pn + k = (6 k + 1)n + k = (6 a + 1) b + a = 6 a b + b + a


      If p = 6 k - 1, and b = n, and a = k,
      then
      pn - k = (6k-1)n - k = (6 a - 1) b - a = 6 a b - b - a




      > I wish to know if in your opinion this proposition is right or wrong.
      > Kind regards,

      Seems to be an algebraic identity.



      > Alberto Zelaya


      Kermit Rose
    Your message has been successfully submitted and would be delivered to recipients shortly.